PERT era, race‐based healthcare disparities in a large urban safety net hospital - Veena H. Dronamraju; Ka U. Lio; Rohan Badlani; Ke Cheng; Parth Rali (Pulmonary Circulation, 2023)
Abstract Pulmonary embolism (PE) is the third leading cause of cardiovascular death in the United States. Black Americans have higher incidence, greater clot severity, and worse outcomes than White Americans. This disparity is not fully understood, especially in the context of the advent of PE response teams (PERT), which aim to standardize PE‐related care. This retrospective single‐center cohort study compared 294 Black and 131 White patients from our institution's PERT database. Primary objectives included severity and in‐hospital management. Secondary outcomes included length of stay, 30‐day readmission, 30‐day mortality, and outpatient follow‐up. Clot  (p = 0.42), acute treatment (p = 0.28), 30‐day mortality (p = 0.77), 30‐day readmission (p = 0.50), and outpatient follow‐up (p = 0.98) were similar between races. Black patients had a lower mean household income ($35,383, SD 20,596) than White patients ($63,396, SD 32,987) (p < 0.0001). More Black patients (78.8%) had exclusively government insurance (Medicare/Medicaid) compared to White patients (61.8%) (p = 0.006). Interestingly, government insurance patients had less follow‐up (58.3%) than private insurance patients (79.7%) (p = 0.001). Notably, patients with follow‐up had fewer 30‐day readmissions. Specifically, 12.2% of patients with follow‐up were readmitted compared to 22.2% of patients without follow‐up (p = 0.008). There were no significant differences in PE severity, in‐hospital treatment, mortality, or readmissions between Black and White patients. However, patients with government insurance had less follow‐up and more readmissions, indicating a socioeconomic disparity. Access barriers such as health literacy, treatment cost, and transportation may contribute to this inequity. Improving access to follow‐up care may reduce the disparity in PE outcomes.